Morphological Differences between Chaetodon auriga and Chaetodon vagabundus based on Truss Morphometric Characters - Rosewitha Anggraeni Privieshanti Hadi; Elly Tuti Winarni; Dian Bhagawati; Agus Nuryanto (Biosaintifika: Journal of Biology & Biology Education, 2021)
Chaetodon auriga and Chaetodon vagabundus are popular marine aquaria fish from Cahetodontidae family. Both species show subtle morphological variations, especially in juvenile stages, which might lead to misidentification. Additional morphological characteristics, such as truss morphometric, are valuable characters for species identification in Chaetodontidae. This study aimed to evaluate morphological differences between Chaetodon auriga and C. vagabundus based on truss morphometric characters. The study is expected to provide new morphometric characters for Chaetodon auriga and C. vagabundus differentiation on the southern coast of West Java, Indonesia. Fish samples were collected from Ujunggenteng and Taman Manalusu Beach. The specimens were identified based on morphological characteristics and referred to the characters available in the literature. Truss morphometric characters were measured using callipers with an accuracy of 0.01mm and convert to ratio values to obtain constant value. The data were analyzed statistically using the Mann-Whitney test in SPSS software packages. The result showed that five truss morphometric characters were significantly different between C. auriga and C.vagabundus.  This study concluded that C. auriga and C. vagabundus could be differentiated using truss morphometric character. This study provides five new morphometric characters for species differentiation in fish species, especially between C. auriga and C. vagabundus.